3C 84: a possibly precessing jet in 43-GHz observations. Issue 4 (19th March 2021) - Dominik, Rune M; Linhoff, Lena; Elsässer, Dominik; Rhode, Wolfgang
ABSTRACT: The central galaxy of the Perseus galaxy cluster, 3C 84 or NGC 1275, hosts one of the closest and well-observed active galactic nuclei (AGNs) and thus offered insights into a variety of phenomena over the past decades. Although close and well observed, some key properties of 3C 84 remain unknown. One of these properties is the inclination angle between the jet and the line of sight, for which a wide range of values can be found in publications. Previous studies have indicated a precessing behaviour of 3C 84's jet that could explain these discrepancies. In this work, we analyse this behaviour at parsec scales using VLBA-BU-BLAZAR Program 43-GHz data. To obtain the position angles necessary to deduce the precessing motion, we use a primary component analysis to extract angles from the available images. The model parameters are estimated through Bayesian Inference. A clear change in the position angle is visible in our data, consistent with a precession. For a pure, non-relativistic precession model, we find a precession frequency of (12.5 ± 1.8)° yr −1 . We further test the possibility of an additional nutation but can, so far, not obtain conclusive results.